Horvátország európai integrációja a makroökonómiai mutatók tükrében - Kotosz, Balázs (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The collapse of communist economies in Eastern Europe and former Soviet Union, as well as their subsequent transition towards market economies, was arguably one of the most far-reaching economic events of the 20lh century. Pain accom panied the economic transition process; all countries experienced a major fall in output after the start of reforms. The growth performance in transition economies was widely different by countries. The paper is looking for the reasons of the growth differences. Even if the initial conditions did not give the same possibilities to governments, early reforms has opened the way to market processes, which seems to be more efficient than state owned institutions in transition economies. In this context, the lower is the state participation, the highest is growth. Empirical analyses justify that GDP growth is higher in countries where state reallocation is decreasing and where tight fiscal policy has been kept.)